2016
DOI: 10.34105/j.kmel.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management adoption and its impact on organizational learning and non-financial performance

Abstract: This paper aims to investigate the determinants of knowledge management (KM) adoption on organizational and individual level, as well as its impact on non-financial performance through an intermediary of organizational learning (“OL”). The KM adoption model was constructed by using a combination of TOE (Technology, Organizational and Environment) for the organizational level and TPE (Technology, Personal, and Environmental) framework for the individual level; this we called the TOPE (Technology, Personal, Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The environmental context is concerned with the organization's size and organization's structure, the organization's competitors, the macroeconomic context, and the regulatory environment. Based on the [43] definition, the environmental context is all regards to the platform where the organization operates, it describes the environmental situations in which the organization conducts the services [6], [44]. Accordingly, It includes the structure of the organization's competitors and regulatory environment [43].…”
Section: Environmental Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental context is concerned with the organization's size and organization's structure, the organization's competitors, the macroeconomic context, and the regulatory environment. Based on the [43] definition, the environmental context is all regards to the platform where the organization operates, it describes the environmental situations in which the organization conducts the services [6], [44]. Accordingly, It includes the structure of the organization's competitors and regulatory environment [43].…”
Section: Environmental Contextmentioning
confidence: 99%
“…One of the most important of these investments is in the e-learning environment to support teaching and learning [1]- [4]. Recently, e-learning has become one of the most critical technologies in terms of competition among higher education institutions (HEIs) toward reducing cost and motivating more students as well as fulfilling their educative obligations [5], [6]. A study by [7] has indicated that around 70% of higher education institutes adopt e-learning and they believe that e-learning is the future of education and the education organizations should pay more attention to e-learning for their longterm strategy.…”
Section: Introductionmentioning
confidence: 99%